Influence of Human Resources Management Practices on Organisational Performance of Construction Firms in Lagos State – Nigeria - Jimoh, Richard; Ihedigbo, Kingsley; Oyewobi, Luqman (International Journal of Sustainable Construction Engineering and Technology, 2023)
The success of any organisation depends on the effective and efficient utilisation of its human resources. In every project-based industry, such as the construction industry, project performance is tied to the effectiveness of its human resources. Labour turnover in the Nigerian construction industry and the poor performance of the Nigerian construction industry in terms of project delay, cost uncertainty, and quality deficiency is caused by inadequate utilisation of human resources management practices. The study aimed to assess the influence of human resources management practices on the organisational performance of construction firms in Lagos State in order to improve their competitive edge. A quantitative research method was adopted involving administration of 140 well-structured questionnaires to registered construction firms. The results revealed that human resources management practices (selection, training, development and reward) have a positive and statistically significant influence on organisational performance, with a p-value of